GENDER AND EDUCATIONAL LEVEL AS PREDICTORS OF INCIDENCE OF BODY DYSMORPHIA AMONG YOUNG ADULTS IN OWERRI - Nwaebube Chukwuka, Nwamaka; Cornelius Uwaoma, Nkwam (African Journal of Social and Behavioural Sciences, 2024)
This study investigated gender and educational level as factors predicting the incidence of body dysmorphia (BD) among young adults in Owerri. Nine hundred and nineteen (914) young adults comprising 447 males and 467 females aged 18 - 25 years with a mean age of 20.77 years and standard deviation of 2.18 were sampled from Owerri, via cluster sampling and random sampling techniques. Three hypotheses guided this work and data was collected using the Body Dysmorphia Questionnaire (BDQ). The data collected, was analyzed via descriptive statistics and regression analysis. The results of the present study revealed that gender predicted the incidence of BD among young adults. Educational level predicted the incidence of BD. Together, gender and educational level predicted the incidence of BD among young adults in Owerri. Discussions were made based on the findings of the current study and the literature. A critical recommendation of this work is that health professionals and clinical psychologists should adopt a comprehensive and individualized approach to screening and treating BD, taking into account patients’ sociodemographic factors especially gender and educational background. This includes incorporating questions and assessments that explore how these factors influence patients’ body image perceptions and tailoring interventions to address specific pressures and challenges faced by different demographic groups. Another recommendation is that counselors should offer culturally sensitive and gender-responsive counselling that acknowledges and addresses the unique societal and educational pressures influencing BD. Hence, to ensure that treatment plans are relevant and effective, the individual’s specific context and experiences should be considered.